Not All Indexical Cues Are Equal: Differential Sensitivity to Dimensions of Indexical Meaning in an Artificial Language. Issue 3 (20th May 2020) - Rácz, Péter; Hay, Jennifer B.; Pierrehumbert, Janet B.
Abstract: In this study, we investigated the learning of indexical features by English‐speaking adults using a novel experimental paradigm. In a conceptual replication of Rácz, Hay, and Pierrehumbert (2017), participants learned an allomorphy pattern cued by a given social context. The social contexts were represented by conversation partners who differed by age, ethnicity, and/or gender and were positioned in various ways. The results showed that, after training, the participants were able to learn that different types of conversation partners prefer different types of allomorphs but that learning and generalization hinged on the social relevance of the cue represented by the conversation partner. These results suggest that the relevance of cues in an individual's past social experience influences their storage and learnability even at very early stages of learning a word pattern. Abstract :